Co-Action of Ionic Liquids with Alternative Sorbents for Removal of Reactive Azo Dyes from Polluted Wastewater Streams - Kamenická, Barbora; Matelová, Kateřina; Pouzar, Miloslav; Weidlich, Tomáš (MDPI, 2024)
In this study, the facile removal of the chromium-complex-based reactive azo dye C. I. Reactive Black 8 (RB8) from model wastewaters by the co-action of alternative sorbents-biochar (BC) and bentonite (BT)-with ionic liquids such as benzalkonium chloride (BAC) or Aliquat 336 (A336) was studied. The experiments using model RB8-containing wastewater proved that the co-action of BAC with BC is the most promising method of RB8 separation from wastewater containing 1 g L-1 of RB8 dye. The application of 2 g L-1 BC in co-action with 1.5 g L-1 BAC or 1 g L-1 BT in co-action with 2 g L-1 BAC enables the removal of more than 98% of contaminant RB8 after 30 min of action. Similar removal efficiency (RE) was achieved using 40 g L-1 of powdered activated carbon (PAC) after 180 min of action. To reach the same RE using real RB8-containing wastewater, a four times higher dose of BC and a four times higher dose of BAC per gram of removed RB8 were required. The proposed mechanism of RB8 removal by the co-action of alternative sorbents with BAC comprises a parallel effect of (i) sorption, (ii) the formation of less polar ion pairs accompanied by their sorption on an alternative sorbent and (iii) the separation of used alternative sorbents covered with ion pairs. The removal efficiency of organic contaminant(s) from both model and real wastewater was evaluated by VIS spectroscopy applying the Lambert-Beer law and by the determination of chemical oxidation demand (COD) and/or adsorbable organically bound halogen (AOX) parameters.
Spolupůsobení iontových kapalin s alternativními sorbenty při odstraňování reaktivních azobarviv z kontaminovaných vod.
Keywords: ionic liquids; biochar; bentonite; sorption; ion exchange; reactive dyes; azo dyes; reactive black 8; iontové kapaliny; biochar; biouhel; bentonit; sorpce; iontová výměna; reaktivní barviva; azobarviva; Reactive Black 8; Ostazinová čerň H-N